USAHA-USAHA CHINA MENYEKAT PENJAJAHAN PERANCIS DI VIETNAM PASCA PERJANJIAN SAIGON 1874 - Dar, Ku Boon (SEJARAH: Journal of the Department of History, 2017)
The Treaty of Saigon, signed on March 15, 1874, stated that Vietnam recognized the full sovereignty of France over Cochin China (South Vietnam). Although France returned Hanoi, the Vietnamese emperor was edgy and sought assistance from China. Consequently, both France and China claimed sovereignty over Vietnamese territory. China move to address the conflict in Vietnam generated polemics among the Chinese mandarin officers who sought to obtain a comprehensive resolution. However, a dispute arose among them and led to a different solution. This article attempts to examine China’s various approaches in this conflict and, secondly considers the extend to which it prevented France from disrupting the protectorate relationship that existed between China and Vietnam under the tributary system. By looking at the response of the Chinese government towards Vietnam’s disputed sovereignty and its efforts to prevent French colonisation, this study help us to understand the relevance of the tributary system as a mechanism of Sino-Vietnamese relations even though it had existed for centuries ago and was being challenged in that crucial era.